Family Support and Self-Agency in the Psychosocial Adaptation of Chronic Kidney Failure Patients Undergoing Hemodialysis: Literature Review - Oktaviani, Anisa; Budhiana, Johan; Novianty, Lia (Lembaga Teewan Journal Solutions, 2026)
Patients with chronic kidney disease (CKD) undergoing hemodialysis often face various physical and psychosocial problems that can affect their anxiety levels and quality of life. Important factors in helping patients adapt psychosocially to their condition and treatment are family support and self-efficacy, such as self-efficacy and self-care. Focusing on quality of life and anxiety levels, this study investigates the role of family support and self-efficacy in the psychosocial adaptation of CKD patients undergoing hemodialysis. This study uses a literature review of ten relevant scientific articles published between 2021 and 2025, which were analyzed descriptively and obtained from the Google Scholar, PubMed, ScienceDirect, and MDPI databases. Descriptive analysis was performed on selected articles. The results of the literature review showed that good family support, high levels of self-efficacy, and self-care abilities were associated with lower anxiety levels and better quality of life in CKD patients undergoing hemodialysis. These findings confirm that improving psychosocial adaptation can be achieved through the use of a holistic nursing approach that involves the family and strengthens the patient's self-agency